ASUHAN KEPERAWATAN MASALAH PSIKOSOSIAL GANGGUAN CITRA TUBUH PADA Tn.N DENGAN KUSTA DI KELURAHAN LIMO KOTA DEPOK - Devi Agustina (2023)
Background : The purpose of this study is to provide an overview of nursing care for Mr. N with psychosocial problems of body image disturbance in the RT 02 RW 07 Limo Village, Depok City. N with psychosocial problems of body image disturbance in the RT 02 RW 07 area of Limo Village, Depok City. The research method used in this research is descriptive research with a case study research design. The results of this study are the assessment conducted found predisposing factors, precipitating factors, signs and symptoms, coping sources, coping mechanisms. Predisposing factors found in patients are changes in limbs due to leprosy and precipitation factors are ostracized by their neighbors. Three nursing diagnoses were successfully established, namely Body Image Disorder, Chronic Low Self Esteem, and Ineffective Coping. Interventions were successfully provided based on the priority of nursing diagnoses, which were first carried out for the problem of body image disturbance and continued for the problem of chronic low self-esteem. Body Image Disorder, Chronic Low Self Esteem, and Ineffective Coping. Based on the results of the nursing evaluation that has been carried out, it can be concluded that the nursing care given to Mr. N with nursing diagnoses of body image disturbance. N with nursing diagnoses of body image disturbance and chronic low self-esteem has improved the patient's condition. Nursing implementation carried out with body image and self-esteem promotion interventions, as well as appropriate implementation strategies, is able to improve the patient's body image and self-esteem. Keywords: nursing care, body image psychosocial problems, leprosy